Optimalisasi Profitabilitas Melalui Kesehatan Finansial dan Pertumbuhan: Peran Moderasi Board Size Pada Perusahaan Sektor Property & Real Estate - Faradila, Afrida Fifin; Suwandi; Utami, Yuni (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
The property and real estate sector is pivotal to Indonesia's economic framework, but it has exhibited a paradoxical decline in Return on Assets (ROA) from 5.2% to 3.8% between 2020 and 2023, despite concurrent sales expansion. This profitability quandary underscores the imperative to reassess its determinants by incorporating corporate governance factors. The objective of this study is to analyze the effects of liquidity, solvency, sales growth, and working capital efficiency on ROA, with board size as a moderating variable. This research utilizes 153 panel data observations from 31 IDX-listed firms (2020–2024) and applies Moderated Regression Analysis to examine the relationships. The results show that liquidity and sales growth do not have a significant influence on ROA. In contrast, solvency and working capital efficiency are found to be significantly and negatively associated with ROA. In addition, board size has a negative moderating effect on the solvency-ROA relationship, but exerts a positive moderating influence on the link between working capital efficiency and ROA.